Microwave-assisted drying of biomaterials - Valerie Orsat (2018)
Drying of biological materials such as fruits and vegetables provides shelf-stable commodities ensuring food security and ease of distribution. There exists numerous drying processes available for the adequate drying of bio-materials. Applying microwave energy to a drying process provides an efficient means of transferring energy for moisture removal. A review of recent microwave assisted drying applications is presented here along with research results on drying of carrots under varying microwave power modes and the comparative drying of mushrooms by microwave/convection and microwave/vacuum. © 2007 Institution of Chemical Engineers.